Nutritional characterization of arabica coffee accession from Ethiopia - dos Santos, Tiago Benedito; Santos, Tiago Benedito; Meda, Anderson Rotter; Sitta, Renata Barrufaldi; Vespero, Eduardo Brandalize; Pavan, Marcos Antônio; Charmetant, Pierre; Carpentieri- Pípolo, Valéria; Pereira, Luiz Filipe Protasio; Vieira, Luiz Gonzaga Esteves; Domingues, Douglas Silva (Coffee Science - ISSN 1984-3909, 2015)
Due to the increasing need for cultivars with high yield and low environmental impact, the introgression of traits related to nutrient utilization efficiency is an important strategy for coffee breeding. In this way, the characterization of accessions from the center of origin is an important tool for breeding programs to gain insight on relevant genotypes with potential interest for production of new cultivars. This work aims to characterize nutrient concentration in 12 Coffea arabica L. wild accessions from Ethiopia, in greenhouse conditions, in order to identify genotypes displaying differential accumulation of mineral nutrients in leaves, shoots and roots. Based on the established criteria, Ethiopian access E237/CAF032 showed differential accumulation for P in leaves and E565/CAF009, E386/CAF131 and E332/CAF023 displayed more accumulation of N, Zn and Mn in roots, respectively. This study identifies one accession with potential more P use efficiency and one accession with potential more N use efficiency, which is an important contribution to identify C. arabica wild genotypes with potential traits related to nutritional efficiency.